Volatilitas Pendapatan terhadap Ketahanan Keuangan Petani di Desa Tegalrejo Blitar Pasca Pandemi Covid-19 - Arma Yuli Fitriasari; Filzah Primardiningtyas; Rafa Syahrul Amrulloh; Maria Yovita R Pandin (Journal of Management and Social Sciences, 2023)
Economic activity in Indonesia affects the level of state income. One sector that makes a large contribution to national income is the agricultural sector. In addition, this sector also contributes in terms of absorbing labor in the provision of food and provision of raw materials. Thus, this article discusses how the Covid-19 pandemic can affect the rise and fall of the financial resilience of farmers, the volatility of income before and after the pandemic, especially for farmers in Tegalrejo Village, Blitar Regency. The purpose of this research is to find out how farmers maintain their economy amidst storms such as Covid-19, transition, pests. The method of analysis used is descriptive qualitative by conducting interviews with farmers to obtain data. From the objectives and methods that have been used, it is known that every farmer in Tegalrejo Village has different income from one another, especially when the Covid-19 Pandemic hit and after the pandemic. In addition, many factors also affect the rise and fall of farmers' income.